3d Modeling of Additive Manufacturing Process: The Case of Polymer Laser Sintering - Siginer, D (American Society of Mechanical Engineers, 2020)
This work focusses on studying multiphysical transient phenomena in polymer powders occurring during selective laser sintering in polymers powders. Multiple phenomena stemming from the interaction of the laser with the polymer powder bed and the transfer of the laser power to the powder bed including laser scattering and absorption, polymer heating, melting, coalescence, densification, and the variation of the material parameters with the temperature are simulated via the modified Monte Carlo-ray tracing method coupled with the Mie theory. A finite volume method is adopted for the heat transfer. The model couples heat diffusion, melting, coalescence and densification of the polymer grains, and the crystallization kinetics during the cooling steps. Laser intensity is concentrated on the surface of the material contrary to the predictions of the Beer-Lambert law. Laser acting on thermoplastic material cause the polymer powder melt, coalescence between melted grains, air diffusion versus densification, crystallization and volume shrinkage. All these processes are simulated by a series of multiphysical models. The reliability of the modeling is tested by comparison with experiments in the literature, and a parametric analysis is performed, based on the process characteristics such as laser sweep speed, its intensity and shape, polymeric grain size among others. Several recommendations to optimize the process are proposed. © 2020 ASME.